Resiliensi mahasiswa ditinjau dari pemaafan dan sifat kepribadian agreeableness - Saputro, Iswan; Nashori, Fuad (Jurnal Psikologi Islam, 2017)
College students report experiencing psychological distress and interpersonal problem. Resilience as a protective factor required to help students reduce the negative effects of psychological distress and promote adaptation. The study aimed to identify the relationship between resilience, forgiveness, and agreeableness among college student. The number of subjectin this study were 211 college students agedbetween 17 to 23 years. Data collection method was conducted using Connor-Davidson Resilience Scale (CD-RISC) (Cronbach’s alpha= 0,89) developed by Connor and Davidson (2003), forgiveness scale (Cronbach’s alpha= 0,935) and agreeableness scale (Cronbach’s alpha= 0,743) developed by Nashori (2017). The data analysis used multiple linear regression tests. Results showed that there was a significant correlation toward the university student resilience in terms of forgiveness and agreeableness (p= 0,000; F= 13,319), a significant positive correlation between resilience with forgiveness (p= 0,003; r= 0,201) and also with agreeableness (p= 0,000; r= 0,326).